LEARNING MEDIA OF TUNAGRAPHITA CHILDREN (CASE STUDY OF MODERATE TUNA AT MANDIRI KUNINGAN TUNA SLB) - Rinrin Riani28 (Universitas Muhammadiyah Kuningan, 2023)
Tuna Mandiri Kuningan Special School (SLB) is one of the schools for children with special needs in Kuningan. There are several class categories in the Kuningan Tuna Mandiri SLB. The mentally retarded class is moderately mentally retarded. The focus of this research is moderately mentally retarded children. Moderate mental retardation is a child who has low thinking ability, weak attention and memory, easily distracted concentration, and easily bored attitude. In general, children experience disorders of the central nervous system so that their fine motor skills experience problems. Visual-based media is media that only relies on the sense of sight. Visual-based media (images or parables) play a very important role in the teaching and learning process. Visual media can facilitate understanding and strengthen memory. Visual-based learning media is learning media that is used in SLB Tuna Mandiri in moderate mental retardation classes. So far, lessons using real images are taught by teachers with direct learning methods. Due to the limitations possessed by Moderately Mentally Disabled Children, it makes the child's incomprehension to illustrate something taught by the teacher. Children with special needs are children who are born with special needs that are different from humans in general, so they need special services. Someone who has an intellectual disability is certain that he is mentally retarded. Children with mental retardation have a tendency to care less about their environment, both in the family and in the surrounding environment. Society generally recognizes mental retardation as mentally retarded or mentally retarded or an idiot. According to Kustawan, D. (2016) is a child who has significantly below average intelligence and is accompanied by an inability to adapt behavior that appears during development. He also said that children with mental retardation have such academic barriers that their learning services require curriculum modifications to suit their special needs. In line with Kustawan's opinion that children with mental retardation have obstacles in processing learning for children in general. And this is where the role of learning media is very helpful in the learning process in class, learning media is also very helpful in the active learning of mentally retarded children. Media that is suitable for use in class is visual media.